Analysis and Identification of Weeds in 3-Month-Old Acacia crassicarpa Stands at PT. Arara Abadi Rasau Kuning District - Lestari, Ika; Ervayenri; Arnaldo , Putra; Ikhsani, Hanifah; Sadjati, Emy (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Acacia crassicarpa is a cultivated species in the Industrial Plantation Forest at PT. Arara Abadi, particularly in the Rasau Kuning District. One of the limiting factors for the growth of Acacia crassicarpa stands is weed infestations. At three months of age, weed infestations increased and became uniform across the Acacia crassicarpa stand area. To ensure that weed control measures yield effective and efficient results, it is essential to base these measures on information regarding the types and composition of weeds in the Acacia crassicarpa area. Therefore, this study aimed to analyze and identify the types of weeds found beneath the Acacia crassicarpa, which is three months old. This research method employs purposive sampling to select locations with dense weed populations for use as study plots. The analysis and identification of the weeds revealed nine species, including Goletrak (Borreria alata), which was the most prevalent, with 50 individuals recorded. Other species identified include Bundung (Cyperus odoratus), Wild Acacia, Ruas-ruas, Ramiding (Stenochlaena palustris), Sword Fern (Nephrolepis biserrata), Alang-alang (Imperata cylindrica), and Meniran (Phyllanthus urinaria). The range of the KR values was between 0.5% and 25.3%, while the FR values ranged from 2.4% to 14.6%. The BKR values varied from 0.3% to 18.8%, and the INV values ranged from 3.5% to 56.0%. The highest SDR value for Borreria alata was 18.7%, indicating significant dominance within the weed community. The Shannon-Wiener diversity index (H') was calculated at 1.96, categorizing it as a moderate level of diversity. Simpson's dominance index (D) was measured at 0.15, suggesting a stable level of weed dominance. Additionally, the Margalef species richness analysis (R1) results yielded a value of 1.51, indicating a low level of species richness among the weeds.